Metalloporphyrins Based Semiconducting Thin Films Deposition And Characterization For Organic Field Effect Transistor - Tan, Pi Lin (2017)
Porphyrins are suitable for their use as the active layer of the organic field-effect transistor (OFET), as they can be easily tailored and they possess a large conjugated π system and good film-forming properties. Various types of porphyrins were selected for this study, i.e., Octaethyl–21H, 23H–Porphine (OEP), Octaethyl–21H, 23H–Porphine Copper (II) (OEP-Cu), Octaethyl–21H, 23H–Porphine Nickel (II) (OEP-Ni), Octaethyl–21H, 23H–Porphine Zinc (II) (OEP-Zn), protoporphyrin IX Zinc (II) (Proto-Zn) and protoporphyrin IX Cobalt Chloride (Proto-Co). All the porphyrins were characterised using the field emission scanning electron microscope (FESEM), Fourier transform infrared (FTIR) and ultraviolet – visible (UV–Vis) analysis. In this research, the organic field-effect transistor devices were prepared by the solution deposition methods (i.e., drop casting and spin coating techniques). The concentrations of the porphyrins used are ranged from 0.05 to 10.0 mg/ml (depending on the solution deposition method). The device with a top contact source and drain structure was selected for spin coating method and bottom contact structure was selected for drop casting method. The Aluminium source and the drain were produced after the thermal evaporation process. The effects of the metalloporphyrins on the electrical properties of the spin-coated organic field-effect transistors, the effects of annealing, the effectiveness of benzocyclobutene as a potential dielectric layer for organic field-effect transistors and the silane adhesion promoter surface treatment on the performance of the diode and the OFET device were also investigated. It was found that the spin coating technique is more suitable as compared to the drop casting technique in the preparation of the porphyrins thin film, due to its better thickness uniformity. In addition, thin film spun coated at concentration blow 3.00 mg/ml and with the gap size of 50μm exhibited the lowest current density of 1.12 A/m2 as compared to the drop casted thin film with the highest current density of 2.77 x 10-5 A/m2 at 5.0V. From the I-V results, the current density of metalloporphyrin is higher than Octaethyl–21H, 23H–Porphine, especially in the presence of silane adhesion promoter. Metalloporphyrins thin film did not shows current leakage in the current density measurement. This makes Octaethyl–21H, 23H– Porphine-Zinc, Octaethyl–21H, 23H–Porphine-Copper and Octaethyl–21H, 23H– Porphine-Nickel are capable to form good quality thin film at low solution concentration. Nevertheless, compared to protoporphyrins (i.e. Proto-Zn and Proto-Cu), both Octaethyl–21H, 23H–Porphine and metalloporphyrins (i.e., OEP-Zn, OEP-Cu and OEP-Ni) do not show good interactions with indium tin oxide (ITO) substrate. Proto-Zn thin film achieved good electrical properties even with low concentration. The protoporphyrins thin film exhibited smoother surface morphology and lower surface roughness compared to the other porphyrins thin films. From the I-V test conducted from voltage ranged -40.0V to 40.0V, benzocyclobutene thin film showed very low current density, no voltage breakdown and high resistivity. This indicates that BCB is suitable to be used as dielectric layer. Based on the Fourier transform infrared analysis, it was found that silane could form interfacial interaction between protoporphyrins and indium tin oxide substrate.